STUDY OF ELECTRICAL PROPERTIES OF A TRIPLE JUNCTION SOLAR CELL TYPE GAAS/GAINP/GE - Souleman, Hasan; Eddine, Adnan (Latakia University Journal -Basic Sciences Series, 2018)
The aim of this search is to study electrical properties of GaAs/GaInP/Ge solar cell in conditions, witch like outer space one. The investigated in our search solar cell consist on three junctions: gallium arsenide, gallium-indium-phosphor and germanium. They have exposed to different doses of electronic beams by Van de Graff accelerator. We obtained curves, witch represent changes of the short circuit current and open circuit voltage of the multi-junction cell device versus the logarithm of the electronic flux and calculated quantities, witch characterize the recombination centers based on extracted in this search experimental data for GaAs/GaInP/Ge solar cell. We found that open circuit voltage of GaAs/GaInP/Ge solar cell varies when we vary the electron flux dose, which varied in the range. Besides, we found that changes of curves, witch represent this property are linear, it means they lines and its slopes in the recombination regime are four times that in diffusion one. In addition, the density of the short circuit current has been measured and we found that it varies linearly too with the electron flux dose according to their qualitative relationships. The obtained results have been compared with those for each individual solar cell, which composes the triple junction solar cell considered in this work. Finally, we estimated quality of the investigated GaAs/GaInP/Ge solar cell and found that values of the maximum power, the fill factor and efficiency oscillated in following ranges, and respectively.